Disability in German-speaking Europe history, memory, culture - Leskau, Linda 1985-; Nusser, Tanja ca. 20./21. Jh; Sorrels, Katherine ca. 20./21. Jh (Studies in German literature linguistics and culture, 2022)
This collection reflects on the development of disability studies in German-speaking Europe and brings together interdisciplinary perspectives on disability in German, Austrian, and Swiss history and culture